Bibliometric and visualization analysis in the field of epigenetics and glioma (2009–2024) - Zeng, Yijun; Tao, Ge; Zeng, Yong; He, Jihong; Cao, Hui; Zhang, Lushun (Frontiers in Oncology, 2024)
IntroductionGlioma represents the most prevalent primary malignant tumor in the central nervous system, a deeper understanding of the underlying molecular mechanisms driving glioma is imperative for guiding future treatment strategies. Emerging evidence has implicated a close relationship between glioma development and epigenetic regulation. However, there remains a significant lack of comprehensive summaries in this domain. This study aims to analyze epigenetic publications pertaining to gliomas from 2009 to 2024 using bibliometric methods, consolidate the extant research, and delineate future prospects for investigation in this critical area.MethodsFor the purpose of this study, publications spanning the years 2009 to 2024 were extracted from the esteemed Web of Science Core Collection (WoSCC) database. Utilizing advanced visualization tools such as CiteSpace and VOSviewer, comprehensive data pertaining to various aspects including countries, authors, author co-citations, countries/regions, institutions, journals, cited literature, and keywords were systematically visualized and analyzed.ResultsA thorough analysis was conducted on a comprehensive dataset consisting of 858 publications, which unveiled a discernible trend of steady annual growth in research output within this specific field. The nations of the United States, China, and Germany emerged as the foremost contributors to this research domain. It is noteworthy that von Deimling A and the Helmholtz Association were distinguished as prominent authors and institutions, respectively, in this corpus of literature. A rigorous keyword search and subsequent co-occurrence analysis were executed, ultimately leading to the identification of seven distinct clusters: “epigenetic regulation”, “DNA repair”, “DNA methylation”, “brain tumors”, “diffuse midline glioma (DMG)”, “U-87 MG” and “epigenomics”. Furthermore, an intricate cluster analysis revealed that the primary foci of research within this field were centered around the exploration of glioma pathogenesis and the development of corresponding treatment strategies.ConclusionThis article underscores the prevailing trends and hotspots in glioma epigenetics, offering invaluable insights that can guide future research endeavors. The investigation of epigenetic mechanisms primarily centers on DNA modification, non-coding RNAs (ncRNAs), and histone modification. Furthermore, the pursuit of overcoming temozolomide (TMZ) resistance and the exploration of diverse emerging therapeutic strategies have emerged as pivotal avenues for future research within the field of glioma epigenetics.